2018
DOI: 10.1016/j.eap.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency of small and medium manufacturing firms in Vietnam: A stochastic meta-frontier analysis

Abstract: Small and medium-size enterprises (SMEs) play a vital role in the Vietnamese economy; hence more understanding of their efficiency is of interest for a variety of various stakeholders in Vietnam. This paper estimates technological gaps and identifies factors affecting variations in the technical efficiency of SMEs in Vietnam using firm-level survey data in 2008 in a stochastic meta-frontier framework. We found that, on average, SMEs can increase their current outputs by eight percent using the same quantity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
5
29
0
Order By: Relevance
“…Besides the topics that received more coverage in the 2008-2018 period, there are some important topics that pale in comparison. In the past 11 years, there have only been three research articles that can be classified into the topic Technology Application (Hoang & Swierczek, 2008;Le, Vu, & Nghiem, 2018;Van Huy, Rowe, Truex, & Huynh, 2012). However, there has been no study on artificial intelligence, machine learning, or computational entrepreneurship.…”
Section: Research Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the topics that received more coverage in the 2008-2018 period, there are some important topics that pale in comparison. In the past 11 years, there have only been three research articles that can be classified into the topic Technology Application (Hoang & Swierczek, 2008;Le, Vu, & Nghiem, 2018;Van Huy, Rowe, Truex, & Huynh, 2012). However, there has been no study on artificial intelligence, machine learning, or computational entrepreneurship.…”
Section: Research Topicsmentioning
confidence: 99%
“…However, there has been no study on artificial intelligence, machine learning, or computational entrepreneurship. What is equally disheartening is the findings that Vietnamese SMEs still have poor infrastructure, weak organizational management, and insufficient support from the government (Hoang & Swierczek, 2008;Le et al, 2012), which eventually results in the usage of outdated technology (Le, Vu, et al, 2018).…”
Section: Research Topicsmentioning
confidence: 99%
“…However, Vietnamese academic seems to be left behind. In the past 11 years, there are only three research articles that can be classified into the topic Technology Application (Hoang and Swierczek, 2008;Le et al, 2018b;Le et al, 2012). There are several reasons for the lack of research on technological advancement in Entrepreneurship in Vietnam.…”
Section: Emerging Topicsmentioning
confidence: 99%
“…Therefore, the introduction the ICT into daily financial operations should boost technological progress in MFIs (Mia et al 2018), and that should lead to the better clients and loans monitoring system, better service delivery and financial performance (Kar et al 2018). Finally, using the synergies from MFIs which have highest performance, as Le et al (2018) also suggested, the policymakers could support the transfer of innovations to other MFIs and on that way increase the productivity of the sector as a whole. Finally, this should lead to the higher asset quality and the productivity growth of MFIs.…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%